Study on factors influencing sand migration in wellbores - Liu Shanshan (Advances in Mechanical Engineering)
Accurate sand control design requires that the sand particles that break through the sand control facilities and enter the wellbore can be completely transported to the wellhead to prevent wellbore sand settling and blocking. At present, there are few studies on the migration and deposition of formation sand with a certain particle size distribution (PSD) after entering the wellbore with formation fluid. Most studies do not consider the sand PSD and treat sand particles as pseudo fluid. Therefore, this paper uses CFD-DEM (computational fluid dynamics-discrete element method) coupling method to conduct numerical simulation of sand migration in the wellbore, and obtains the influence rule of fluid velocity, viscosity, well deviation angle, formation sand production concentration, and PSD on cross-section sand concentration (sand carrying capacity of the fluid) and axial pressure drop in the wellbore section. Based on the simulation results and dimensional analysis, a prediction model for the volume concentration of sand particles in the wellbore was established, which is convenient for engineering applications to quickly determine the flow state of the wellbore. An engineering method for determining the critical non-deposition velocity of sand particles in wellbore was proposed, and the critical non-deposition velocity of sand particles under three effective particle sizes, three sand production concentrations, and three fluid viscosities was obtained. The research results can provide a theoretical basis for sand carrying and the production systems coordinated optimization design in weakly consolidated sandstone reservoirs.